Highly efficient radiative recombination in intrinsically zero-dimensional perovskite micro-crystals prepared by thermally-assisted solution-phase synthesis. Issue 71 (8th December 2020) - Xu, Wei-Long; Bradley, Siobhan J.; Xu, Yang; Zheng, Fei; Hall, Christopher R.; Ghiggino, Kenneth P.; Smith, Trevor A.
Abstract : 0D Cs4 PbBr6 perovskite microcrystals exhibit a radiative recombination coefficient two orders of magnitude higher than typical 3D perovskite. Abstract : Zero-dimensional (0D) quantum confinement can be achieved in perovskite materials by the confinement of electron and hole states to single PbX6 4− perovskite octahedra. In this work, 0D perovskite (Cs4 PbBr6 ) micro-crystals were prepared by a simple thermally-assisted solution method and thoroughly characterized. The micro-crystals show a high level of crystallinity and a high photoluminescence quantum yield of 45%. The radiative recombination coefficient of the 0D perovskite micro-crystals, 1.5 × 10 −8 s −1 cm 3, is two orders of magnitude higher than that of typical three-dimensional perovskite and is likely a strong contributing factor to the high emission efficiency of 0D perovskite materials. Temperature dependent luminescence measurements provide insight into the role of thermally-activated trap states. Spatially resolved measurements on single 0D perovskite micro-crystals reveal uniform photoluminescence intensity and emission decay behaviour suggesting the solution-based fabrication method yields a high-quality and homogenous single-crystal material. Such uniform emission reflects the intrinsic 0D nature of the material, which may be beneficial to device applications.